2000
DOI: 10.1111/0002-9092.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Monthly Food Stamp Cycle: Shopping Frequency and Food Intake Decisions in an Endogenous Switching Regression Framework

Abstract: Mean food spending by food stamp households peaks sharply in the first three days after benefits are received. For those who conduct major grocery shopping trips only once per month (42% of all food stamp households), mean food energy intake drops significantly by the fourth week of the month. For the remaining households, intake remains steady over the course of the month. These patterns motivate an empirical model that simultaneously accounts for the shopping frequency and food intake decisions over time. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(161 citation statements)
references
References 8 publications
7
142
1
Order By: Relevance
“…9 For example, studies found that food expenditure and energy intake increased dramatically after food stamps are received. 15,24,25 Cyclical food restriction is associated with an increase in body fat, decrease in lean body muscle mass, and a quicker weight gain. 9 Second, weight cycling due to food insecurity could make the body use the dietary energy more efficiently, such as increasing body fat storage in response to food shortage.…”
Section: Resultsmentioning
confidence: 99%
“…9 For example, studies found that food expenditure and energy intake increased dramatically after food stamps are received. 15,24,25 Cyclical food restriction is associated with an increase in body fat, decrease in lean body muscle mass, and a quicker weight gain. 9 Second, weight cycling due to food insecurity could make the body use the dietary energy more efficiently, such as increasing body fat storage in response to food shortage.…”
Section: Resultsmentioning
confidence: 99%
“…This cycle may predispose people toward purchasing less healthy food items in bulk as opposed to healthier (but perishable) fresh produce. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Nearly all jurisdictions now distribute food stamp and TANF payments on electronic benefit transfer debit cards, so the costs of more frequent payments would be likely to be low. Shapiro (2005), Wilde and Ranney (2000), and Ohls et al (1992) also point out benefits of more frequent payments. Such changes would require legislative action because the law currently requires that food stamp and SSI payments be made in monthly allotments.…”
Section: Discussionmentioning
confidence: 99%